Continual quality improvement for professional engineers qualifications in engineering accreditation programmes / Assoc. Prof. Ir. Dr. Yee Hooi Min - Yee, Hooi Min (Unit Penerbitan FKAPP, 2021)
Engineering Programme Accreditation Standard 2020 stated Engineering Accreditation Council (EAC) is the body delegated by The Board of Engineers Malaysia (BEM) for accreditation of engineering degrees. The EAC is made of representatives of the BEM, The Institution of Engineers, Malaysia (IEM), Malaysian Qualifications Agency (MQA) and the Public Services Department (Jabatan Perkhidmatan Awam Malaysia (JPA). The objective of accreditation is to ensure that graduates of the accredited engineering programmes meet the minimum academic requirements for registration as a graduate engineer with the BEM. In addition, the objective of accreditation is to ensure that Continual Quality Improvement (CQI) is being practiced by Institutions of Higher Learning (IHL). Accreditation may also serve as a tool to benchmark engineering programmes offered by IHLs in Malaysia.